2019
DOI: 10.1111/ans.15049
|View full text |Cite
|
Sign up to set email alerts
|

The role of intraperitoneal ropivacaine in laparoscopic appendicectomy: a prospective, double‐blinded randomized control Australian study

Abstract: Background: Currently, intraoperative use of local anaesthetic is not routinely given in all laparoscopic appendicectomies. Although its use has been widely studied in laparoscopic hernia repairs, gynaecological laparoscopy and laparoscopic cholecystectomies, there are no published trials of the use of intraperitoneal local anaesthetic during laparoscopic appendicectomy in the Australasian setting. The aim of this study was to determine whether the use of intraperitoneal ropivacaine during laparoscopic appendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 12 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, some physicians chose to premedicate their patients with individualized doses of midazolam based on their weight [10][11][12][13]. For anesthesia induction, patients were administered a combination of 1-3 mg/kg propofol, 1-2 μg/kg fentanyl, 0.1 mg/kg vecuronium, 1-1.5 mg/kg suxamethonium, and/or 1-1.5 mg/kg desflurane in oxygen-enriched air mixture, and this was maintained typically with sevoflurane 1-3% with oxygen [11][12][13][14][15][16][17][18]. Alternatively, another study gave their patients 5 mg/kg thiopental and 0.6 mg/kg rocuronium intravenously for anesthesia induction and tracked if they altered pain following surgery [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, some physicians chose to premedicate their patients with individualized doses of midazolam based on their weight [10][11][12][13]. For anesthesia induction, patients were administered a combination of 1-3 mg/kg propofol, 1-2 μg/kg fentanyl, 0.1 mg/kg vecuronium, 1-1.5 mg/kg suxamethonium, and/or 1-1.5 mg/kg desflurane in oxygen-enriched air mixture, and this was maintained typically with sevoflurane 1-3% with oxygen [11][12][13][14][15][16][17][18]. Alternatively, another study gave their patients 5 mg/kg thiopental and 0.6 mg/kg rocuronium intravenously for anesthesia induction and tracked if they altered pain following surgery [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of the wound was also a choice for preoperative pain management. It was done by using levobupivacaine or ropivacaine in the skin and pre-peritoneal space before introducing the ports and then again after the third port was introduced [13,15,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analgesic strategy of local infiltration can provide a strong analgesic effect and reduce the application of opioids after surgery, thereby reducing adverse events and shortening hospitalization (7)(8)(9). A prospective, doubleblinded, randomized, controlled trial in Australia reported by Huang et al (10) showed that the local intraperitoneal injection of ropivacaine had an analgesic effect within 6 h after emergency laparoscopic appendectomy and reduced the dosage of postoperative opioid analgesics. In a prospective randomized control trial, Liang et al (11) studied the efficacy and safety of different doses of ropivacaine for laparoscopy-assisted infiltration analgesia in patients undergoing laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%